Bispecific T-Cell Engaging Antibodies Against MUC16 Demonstrate Efficacy Against Ovarian Cancer in Monotherapy and in Combination With PD-1 and VEGF Inhibition - Yeku, Oladapo O.; Rao, Thapi Dharma; Laster, Ian; Kononenko, Artem; Purdon, Terence J.; Wang, Pei; Cui, Ziyou; Liu, Hong; Brentjens, Renier J.; Spriggs, David (Frontiers in Immunology, 2021)
Immunotherapy for ovarian cancer is an area of intense investigation since the majority of women with relapsed disease develop resistance to conventional cytotoxic therapy. The paucity of safe and validated target antigens has limited the development of clinically relevant antibody-based immunotherapeutics for this disease. Although MUC16 expression is almost universal in High Grade Serous Ovarian Cancers, engagement of the shed circulating MUC16 antigen (CA-125) presents a theoretical risk of systemic activation and toxicity. We designed and evaluated a series of bispecific tandem single-chain variable fragments specific to the retained portion of human MUC16 ectodomain (MUC16ecto) and human CD3. These MUC16ecto- BiTEDs retain binding in the presence of soluble MUC16 (CA-125) and show cytotoxicity against a panel of ovarian cancer cells in vitro. MUC16ecto- BiTEDs delay tumor progression in vivo and significantly prolong survival in a xenograft model of ovarian peritoneal carcinomatosis. This effect was significantly enhanced by antiangiogenic (anti-VEGF) therapy and immune checkpoint inhibition (anti-PD1). However, the combination of BiTEDs with anti-VEGF was superior to combination with anti-PD1, based on findings of decreased peritoneal tumor burden and ascites with the former. This study shows the feasibility and efficacy of MUC16ecto- specific BiTEDs and provides a basis for the combination with anti-VEGF therapy for ovarian cancer.